Optic Nerve Diffusion Tensor Imaging after Acute Optic Neuritis Predicts Axonal and Visual Outcomes - van der Walt, Anneke (Public Library of Science, 2013)
BACKGROUND: Early markers of axonal and clinical outcomes are required for early phase testing of putative neuroprotective therapies for multiple sclerosis (MS). OBJECTIVES: To assess whether early measurement of diffusion tensor imaging (DTI) parameters (axial and radial diffusivity) within the optic nerve during and after acute demyelinating optic neuritis (ON) could predict axonal (retinal nerve fibre layer thinning and multi-focal visual evoked potential amplitude reduction) or clinical (visual acuity and visual field loss) outcomes at 6 or 12 months. METHODS: Thirty-seven patients presenting with acute, unilateral ON were studied at baseline, one, three, six and 12 months using optic nerve DTI, clinical and paraclinical markers of axonal injury and clinical visual dysfunction. RESULTS: Affected nerve axial diffusivity (AD) was reduced at baseline, 1 and 3 months. Reduced 1-month AD correlated with retinal nerve fibre layer (RNFL) thinning at 6 (R=0.38, p=0.04) and 12 months (R=0.437, p=0.008) and VEP amplitude loss at 6 (R=0.414, p=0.019) and 12 months (R=0.484, p=0.003). AD reduction at three months correlated with high contrast visual acuity at 6 (ρ = -0.519, p = 0.001) and 12 months (ρ = -0.414, p=0.011). The time-course for AD reduction for each patient was modelled using a quadratic regression. AD normalised after a median of 18 weeks and longer normalisation times were associated with more pronounced RNFL thinning and mfVEP amplitude loss at 12 months. Affected nerve radial diffusivity (RD) was unchanged until three months, after which time it remained elevated. CONCLUSIONS: These results demonstrate that AD reduces during acute ON. One month AD reduction correlates with the extent of axonal loss and persistent AD reduction at 3 months predicts poorer visual outcomes. This suggests that acute ON therapies that normalise optic nerve AD by 3 months could also promote axon survival and improve visual outcomes.